2010
DOI: 10.3136/fstr.16.395
|View full text |Cite
|
Sign up to set email alerts
|

Content of Selected Flavonoids in 100 Edible Vegetables and Fruits

Abstract: The objective of this work was to quantify the potential anticancer flavonoids (quercetin, kaempferol, isorhamnetin, apigenin and luteolin) by a rapid, reliable and accurate reverse phase high performance liquid chromatography (RP-HPLC) among 100 edible vegetables and fruits commonly consumed in Harbin city, China. The predominant flavonoids found in the largest abundance in all of the analyzed foods were kaempferol, followed by luteolin and quercetin. Potherb mustard, lettuce (red), toona leaf, celery leaf, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 19 publications
0
46
2
Order By: Relevance
“…Soluble and hydrolysable flavonoid contents in this study were lower than those reported by Fategbe et al (2012). The variability in soluble and hydrolysable flavonoid content can depend on the eggplant variety used and the predominant flavonoid type, an observation also point out by Cao et al (2010).…”
Section: Nsmentioning
confidence: 98%
“…Soluble and hydrolysable flavonoid contents in this study were lower than those reported by Fategbe et al (2012). The variability in soluble and hydrolysable flavonoid content can depend on the eggplant variety used and the predominant flavonoid type, an observation also point out by Cao et al (2010).…”
Section: Nsmentioning
confidence: 98%
“…19,20 Flavonoids like apigenin, quercetin, genistein etc., have been shown to exhibit anti-cancer activity while being nontoxic to normal cells. 25 It is non-mutagenic and possesses antimicrobial, antiviral and anti-carcinogenic activities. The -OH and C=O groups present are reported to aid in the reduction of Au 3+ and in the stabilization of the AuNPs formed.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-phase extraction was used to extract eight flavonoids in apple juice through C 18 cartridges, and methanol was selected as elution solvent (Ali et al 2011). In some cases, an acid treatment was applied to hydrolyze the glycosides in order to determine the content of free and conjugated flavonoids as aglycons (Cao et al 2010). Furthermore, synthetic antioxidants such as tertbutylhidroquinone (Sultana and Anwar 2008) or butylated hydroxytoluene (Cao et al 2010) can be added in order to avoid the oxidation of the compounds.…”
Section: Introductionmentioning
confidence: 99%